The Effect of Derivative Transactions on the Value Relevance of Earnings through Corporate Earnings Management in Indonesia - Suhendra Suhendra; Limajatini Limajatini; David Kiki Baringin MT. Samosir (Budapest International Research and Critics University, 2021)
This study aims to examine and analyze the effect of derivative transactions on earnings management, the effect of earnings management on value relevance of earnings, and the effect of derivative transactions on value relevance of earnings. This study uses data from non-financial companies in Indonesia for the period 2013-2017 with 43 sample of companies. In this study, earnings management is calculated based on the Jaggi model. The value relevance of earnings is calculated based on Ohlson's model. The results show that derivative transactions have a positive effect on earnings management. Earnings management negatively affects the value relevance of earnings. Derivative transactions are not proven to have a negative effect on the value relevance of earnings. Derivative transactions, especially those with non-hedging criteria, show a high tendency towards earnings management activities. Derivative transactions have a positive effect on earnings management. With the negative influence of derivative transactions and earnings management activities on the value relevance of earnings, the commissioner or audit committee needs to carry out an internal oversight function in reporting financial statements, especially in non-financial companies that carry out derivative transactions.